Application of microcracked columnar TiO2 thin films deposited by DC hollow cathode plasma jet in dye-sensitized solar cells; Journal of Vacuum Science and Technology A; Vol. 35, iss. 6 - Perekrestov R. V. Roman Vyacheslavovich; Kudrna P. Pavel; Danis S. Stanislav; Tichy M. Milan; Bieloshapka I. Igor; Vladoiu R. Rodica (2017, 2017)
Title screen